Clinical Findings in a Multicenter MRI Study of Mild TBI - Shetty, Teena; Nguyen, Joseph T.; Cogsil, Taylor; Tsiouris, Apostolos John; Niogi, Sumit N.; Kim, Esther U.; Dalal, Aashka; Halvorsen, Kristin; Cummings, Kelianne; Zhang, Tianhao; Masdeu, Joseph C.; Mukherjee, Pratik; et al. (Frontiers in Neurology, 2018)
Background: Uncertainty continues to surround mild traumatic brain injury (mTBI) diagnosis, symptoms, prognosis, and outcome due in part to a lack of objective biomarkers of injury and recovery. As mTBI gains recognition as a serious public health epidemic, there is need to identify risk factors, diagnostic tools, and imaging biomarkers to help guide diagnosis and management. Methods: One hundred and eleven patients (15–50 years old) were enrolled acutely after mTBI and followed with up to four standardized serial assessments over 3 months. Each encounter included a clinical exam, neuropsychological assessment, and magnetic resonance imaging (MRI). Chi-square and linear mixed models were used to assess changes over time and determine potential biomarkers of mTBI severity and outcome. Results: The symptoms most frequently endorsed after mTBI were headache (91%), not feeling right (89%), fatigue (86%), and feeling slowed down (84%). Of the 104 mTBI patients with a processed MRI scan, 28 (27%) subjects had white matter changes which were deemed unrelated to age, and 26 of these findings were deemed unrelated to acute trauma. Of the neuropsychological assessments tested, 5- and 6-Digit Backward Recall, the modified Balance Error Scoring System (BESS), and Immediate 5-Word Recall significantly improved longitudinally in mTBI subjects and differentiated between mTBI subjects and controls. Female sex was found to increase symptom severity scores (SSS) at every time point. Age ≥ 25 years was correlated with increased SSS. Subjects aged ≥ 25 also did not improve longitudinally on 5-Digit Backward Recall, Immediate 5-Word Recall, or Single-Leg Stance of the BESS, whereas subjects < 25 years improved significantly. Patients who reported personal history of depression, anxiety, or other psychiatric disorder had higher SSS at each time point. Conclusions: The results of this study show that 5- and 6-Digit Backward Recall, the modified BESS, and Immediate 5-Word Recall should be considered useful in demonstrating cognitive and vestibular improvement during the mTBI recovery process. Clinicians should take female sex, older age, and history of psychiatric disorder into account when managing mTBI patients. Further study is necessary to determine the true prevalence of white matter changes in people with mTBI.